Rejection of divalent ions in commercial tubular membranes: Effect of feed concentration and anion type - Qadir, D. (Chinese Institute of Environmental Engineering, 2017)
Four commercial tubular membranes (AFC80, AFC30, PU608, and ES404) have been investigated in this study for their performance of binary metal ions rejection under different feed conditions. A range of salts (tin chloride, tin sulphate, calcium chloride, calcium sulphate) with divalent cations were chosen to assess the effects of different anions (chloride and sulphate) on performance of the membranes. All membranes were tested by varying the feed concentration (2500, 5000, 10,000 mg L−1) at fixed cross flow velocity of 1.5 LPM and feed pressure 1400 kPa. Observed retention (Robs) and permeate flux (Jv) were key parameters to evaluate the performance of studied tubular membranes. It was found that increase in concentration adversely affected the both evaluation parameters, i.e., permeate flux and rejection. Nevertheless, nanofiltration type tubular membranes (AFC80 and AFC30) showed higher rejection than their counterparts, i.e., ultrafiltration type tubular membranes (ES404, PU608) for all investigated salts. Maximum observed rejection for all salts was noted for AFC80 for all salts followed by AFC30, ES404 and PU608 tubular membranes. Furthermore, it is reveal that anion types (SO4 2−, Cl−) of these salts played a vital role in retention of these tubular membranes when the salts with same cations were used as feed solution. © 2016 Chinese Institute of Environmental Engineering, Taiwan